Effect of pyrolysis carbon black and carbon nanotubes on properties of natural rubber conductive composites. Issue 23 (10th March 2022) - Yan, Gang; Han, Deshang; Li, Wenchao; Qiu, Jian; Jiang, Chaojie; Li, Li; Wang, Chuansheng
Abstract: Carbon based materials with excellent conductivity such as conductive carbon black, graphene, and carbon nanotubes (CNTs) are often used in the preparation of conductive polymer composites. Pyrolysis carbon black, as a recycled material of waste rubber, can be used as a substitute for other carbon black in some fields, which can greatly reduce the production cost and promote reuse of used rubber. In this article, pyrolysis carbon black is mixed with CNT and added to natural rubber by mechanical blending method to get the composite material. The synergistic effect of pyrolysis carbon black and CNT, 3D network structure and formation of conductive network are investigated, and the properties of composites are analyzed. The results show that the 3D "grape cluster" network structure formed by the synergistic action of the pyrolysis carbon black and CNT, which led to the improvement of the curing properties and mechanical properties of the composites, increase the Payne effect, decrease the dispersion of the filler, and significant reduction the volume resistivity of the composites. With the increasing of CNT content, the variation of the properties of the composites changed and stabilized. In general, when 40 phr pyrolysis carbon black and 4 phr CNT are mixed into rubber matrix, the composite has the best comprehensive performance, and the volume resistivity is 9.25E5. Our results provide new thoughts in preparing natural rubber conductive composites. By adding highly CNT and inexpensive pyrolysis carbon black, the problem of easy aggregation of a single filler is overcome, which is more economical than adding two highly conductive fillers, and the process is simpler and time‐saving compared to the modified solution. More studies need to be done in order to reveal the effects of pyrolysis carbon black in practical conductive composites. Abstract : For the first time, pyrolysis carbon black was blended with CNT for the preparation of conductive composites, which improved the conductivity on the basis of ensuring comprehensive performance. Compared with the preparation of conventional conductive composites, this method can promote the use of thermally cracked carbon black and is more economical and saves production cost.